Modelo de procesos para el desarrollo del front-end de aplicaciones web - Valdivia Caballero, José Jesús (2016)
The phrase ‘divide and rule’ and which proposes a strategy of dividing a centralized power structure into smaller power groups. Based on this principle, this study proposes that in the project management for the development of a web application, where the application’s implementation can be divided in processes with their own tools, resources and life cycle. Both O’Reilly (2007) and Ginige (1998) mention that the technologies to be used in the front-end of a web application are different from those of the back-end, making it possible to decouple the implementation into its own components from the side of the customer or web browser and from the applications servers, databases and static files.